KONTRIBUSI TINGGI BADAN, DAYA LEDAK TUNGKAI DAN KOORDINASI MATA-TANGAN TERHADAP JUMP SMAH FORHAND PERMAINAN BULUTANGKIS PADA SISWA MAN KOTABARU - Jusran S (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2015)
This study aims to determine the contribution of jointly height, explosive leg power and hand-eye coordination to jump smash badminton game forhand students Man Kotabaru. The sample used in this study were 40.The method used in this research is quantitative research methods that are deskriktif which aims to determine whether there is a contribution of height, explosive legs and eye-hand coordination to jump smash forhand badminton game with an instrument of research are: (1) measurement of height by unit cm (2) the test of explosive power tungksi to jump without the prefix by the meter (3) test hand-eye coordination to the test throwing catching sphere is reflected to the wall for 30 seconds (4) the test jump smash forhand by doing jump smash forhand by hitting shutle cock dibwa passes over the net and rope with high distance between the net and the rope 30 cm unit smash incoming number between net and rope with a chance 12 times.These results indicate that: (1) There is a significant contribution between the height of the jump smash forhand skills in students Man Kotabaru with a value of Rº = 0520, or 52.0%. (2) There is a significant contribution between the explosive power of the legs to jump smash forhand skills in students Man Kotabaru with a value of Rº = 0421, or 42.1%. (3) There is a contribution to the hand-eye coordination skills in students jump smash forhand Man Kotabaru with a value of Rº = 0.464 or 46.4%. (4) There is a significant contribution of height, limb explosive power and hand-eye coordination to jump smash forhand on students Man Kotabaru with a value of Rº = 0657, or 65.7%.Keywords: Height, explosive power and leg-Eye Coordination Skills Tagan jump smash forhand